2015
DOI: 10.12691/jfnr-3-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation Patterns of the Volatile Compounds in Flowers of Chinese Native Citrus Species and Their Taxonomic Implications

Abstract: In this study, the volatile compounds in the flowers of nine Citrus species/varieties, seven of which are native to China, were analyzed using headspace-solid phase microextraction (HS-SPME) coupled with gas chromatography mass spectrometry (GC-MS). A total of 94 compounds were identified, including various terpenes, such as monoterpenes, sesquiterpenes, terpene alcohols and aldehydes, which together accounted for 80.4% to 92.4% of the total compounds analyzed. Limonene, linalool and γ-terpinene were the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…These methods provide abundant information, not only for metabolism-related research, but also for chemotaxonomy. Consequently, several studies on Citrus have used this approach [27,28]. The chemotaxonomy of Mangshanyegan (C. nobilis Lour.…”
Section: Introductionmentioning
confidence: 99%
“…These methods provide abundant information, not only for metabolism-related research, but also for chemotaxonomy. Consequently, several studies on Citrus have used this approach [27,28]. The chemotaxonomy of Mangshanyegan (C. nobilis Lour.…”
Section: Introductionmentioning
confidence: 99%
“…Piperitone was the main terpenoid component of green prickly ash fruit, whereas that of red prickly ash fruit was limonene. Citrus is also an economically important tree species in the Rutaceae family, and the main terpenoids in its peel are limonene and myrcene, the same as those of red prickly ash [ 47 ]. The content and composition of terpenoids showed that the aroma of red prickly ash is more similar to that of citrus than is the aroma of green prickly ash.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely loved by consumers because of its unique flavor and rich active substances such as naringin, neohesperidin, and limonin. Recently, the yield has risen to about 200,000 tons, and Huyou juice (HJ) becomes the main variety of citrus in China (Xi, Li, Dong, Jiao, & Zhou, 2015). Flavonoids and phenolics, important bioactive ingredients in HJ, have been shown to reduce blood lipids, improve liver inflammation, and have a probiotic potential known as a prebiotics (Fang, Ruiting, & Zhang, 2015).…”
Section: Introductionmentioning
confidence: 99%